LEVELS DEVELOPMENT IN MOUNTAIN MUNICIPALITIES AND THEIR RELATIONSHIPS IN RESOURCE CONSTRAINTS [CASE STUDIES OF MUNICIPALITIES IN THE AURES REGION] - Khemri Souhila; Meddour Oualid; Redjal Omar (International Journal of Innovative Technologies in Social Science, 2024)
The article examines the levels of development in the mountain municipalities of the Aures region and their relationship to the regional development that the region is experiencing through several indicators that we will discuss in the classification. Since the study area belongs to the Aures massif, where geographical data partially converge, the article aims to understand the elements that led to the change in the image of the (old) mountain area and led to spatial, economic, social, functional, and especially environmental transformations, which have made the region increasingly vulnerable. The regional development in the mountain areas has not been related to industrial development and local economic growth, which has made the urban growth a burden on local development in these areas rather than a factor of progress within them. After discussing the classification of the centers comprising the region, which varied in their levels according to the administrative status, the date of obtaining the promotion, the relationship of the centers to the road axes, and the origin of the establishment, we will discuss the classification of the municipalities based on a set of indicators to search for an explanation of the reality occurring in the study area. We relied on the rank correlation matrix to understand the reasons for the disparities in the level of development among municipalities and to provide analyses of the results reached. We utilized 20 indicators, and the result of development in the municipalities was varied: the municipality of Arris witnessed good development, four municipalities had acceptable development, three municipalities had development from average to weak, and three municipalities had very weak development. The disparities were large, from the highest level to the lowest level of development. Several factors and reasons contributed to the development of some municipalities and the marginalization of others.